2016
DOI: 10.1002/ajh.24350
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic value of hematogones in patients with acute myeloid leukemia

Abstract: In acute myeloid leukemia (AML), new prognostic tools are needed to assess the risk of relapse. Hematogones (HGs) are normal B-lymphocyte precursors that increase in hematological diseases and may influence remission duration in AML. HG detection was prospectively investigated in 262 AML patients to determine its prognostic value. Flow cytometric HG detection was performed in bone marrow aspiration after intensive chemotherapy at the time of hematological recovery. Patients with HGs in bone marrow samples had … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…Hematogones in bone marrow can be more than 5% when hematopoietic function is activated after chemotherapy in neoplasm patients 12 . A few reports have indicated that the frequency of hematogones in bone marrow could be used as a prognosis indicator of AML, childhood ALL and B-cell ALL patients who have received hematopoietic stem cell transplantation, and suggested a better prognosis when hematogones >1% in childhood ALL 1418 . However, it has not been thoroughly discussed whether the levels of hematogones and CD34+ myeloblasts in bone marrow have impact on the prognosis for adult ALL patients who have received chemotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…Hematogones in bone marrow can be more than 5% when hematopoietic function is activated after chemotherapy in neoplasm patients 12 . A few reports have indicated that the frequency of hematogones in bone marrow could be used as a prognosis indicator of AML, childhood ALL and B-cell ALL patients who have received hematopoietic stem cell transplantation, and suggested a better prognosis when hematogones >1% in childhood ALL 1418 . However, it has not been thoroughly discussed whether the levels of hematogones and CD34+ myeloblasts in bone marrow have impact on the prognosis for adult ALL patients who have received chemotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…and MRD (+) groups in AML patients in one of their study (Chantepie et al, 2016). While the presence of HG in the MRD (À) group provides a better PFS and OS, the presence of HG in the MRD (+) group is provides worse PFS and OS.…”
Section: Discussionmentioning
confidence: 94%
“…While HG was not detected in 31 (38.8%) patients, HG was detected in 49 (61.2%) patients. The median HG value in the HG (+) group was found five (Chantepie et al, 2013;Chantepie et al, 2016;D'Arena et al, 2001;Doki et al, 2015;Greipp et al, 2005;Lúcio et al, 1999;McKenna et al, 2001;McKenna et al, 2004;Moreno-Madrid et al, 2008;Muehleck et al, 1983;Palumbo et al, 2015;Palumbo & Anderson, 2011;Sarmiento Palao et al, 2019;Sevilla et al, 2010). The demographic and clinical characteristics of these two groups are summarized in Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…14,15 Superior outcome amongst AML patients with higher level of HGs was observed with both overall survival (OS) and relapse-free survival (RFS). 16 In addition, better RFS and OS rates have been associated with emergence or expansion of HGs in patients after hematopoietic stem cell transplantation (HSCT). [17][18][19][20] Despite the prognostic impact of BM HGs in AML attracting attention recently, [14][15][16] far less is known when it comes to acute lymphoblastic leukemia (ALL).…”
Section: Introductionmentioning
confidence: 99%